Cats as a potential source of emerging influenza virus infections - Horimoto, Taisuke; Gen, Fumihiro; Murakami, Shin; Iwatsuki-Horimoto, Kiyoko; Kato, Kentaro; Hisasue, Masaharu; Sakaguchi, Masahiro; Nidom, Chairul A.; Kawaoka, Yoshihiro (Virologica Sinica, 2015)
<正>Dear Editor,Historically,the influenza virus has not been regarded as a major pathogen of cats.However,since 2003,natural infections of domestic cats with highly pathogenic H5N1 avian virus causing fatal cases have been reported(Songserm et al.,2006;Yingst et al.,2006;Klopfleisch et al.,2007).Furthermore,infections of this animal with A(H1N1)pdm09 virus,causing respiratory illness with some fatal cases,have also been reported in various parts